Effect of Soil Application of Aldrin & Dieldrin on Yield and Chemical Composition of Groundnut (Araohis Hypogaea L.) - Dhindsa, Kuldip Singh; Singhvi, S M; Gupta, S K; Verma, N D (Annals of Arid Zone, 2016)
.